Non-Hodgkin’s Lymphoma of the Breast: An Unusual Case Report - Mandim, Andreia; Couto, Maria Eduarda; Oliveira, Raquel; Santos, Raquel (Brazilian Journal of Case Reports, 2025)
Primary breast lymphoma is a rare condition accounting for less than 0.5% of all breast malignancies. It typically presents as a solitary mass in women aged 50–60, with clinical and imaging features mimicking breast carcinoma. We present the case of a 60-year-old woman with a right breast nodule diagnosed as marginal zone lymphoma (MZL) by histology. The patient was treated with R-CHOP immunochemotherapy followed by radiotherapy, achieving complete remission with 24 months of sustained follow-up. This case highlights the importance of early histological diagnosis, the occasional diagnostic role of surgery, and the controversies surrounding treatment strategies for breast MZL.